2017
DOI: 10.1097/bcr.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Techniques for the Determination of Burn Severity in Real Time

Abstract: Visual diagnosis of second-degree burns has proven inadequate for determining the appropriate treatment regimen. Although multiple noninvasive imaging techniques have shown promise for providing information about burn wound severity, the ideal technology to aid burn wound excision would provide real-time readouts. Herein, the authors examine a high-resolution infrared (IR) camera (thermography) and a multiprobe adapter system (MPAS-6; transepidermal evaporative water loss, colorimetry) to assess their usefulne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
0
14
1
2
Order By: Relevance
“…burns.2018.09.026 time feedback to clinicians. Hand-held systems have recently been commercialized and these are relatively inexpensive [9]. However thermal imaging can be very sensitive to fluctuations in ambient temperature [10] and studies that have directly compared laser Doppler techniques and thermal imaging have found that laser Doppler can be more accurate in terms of categorizing burn severity [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…burns.2018.09.026 time feedback to clinicians. Hand-held systems have recently been commercialized and these are relatively inexpensive [9]. However thermal imaging can be very sensitive to fluctuations in ambient temperature [10] and studies that have directly compared laser Doppler techniques and thermal imaging have found that laser Doppler can be more accurate in terms of categorizing burn severity [8].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to burn wound severity, it is typically used to identify regions of tissue within a burn that demonstrate reduced surface temperature relative to some baseline normal skin surface temperature. The reduction in temperature suggests that in these areas, the underlying blood vessels have been damaged to the point where the lack of perfusion leads to a reduction in thermal emission and this can be empirically related to burn depth [8][9][10]. Recent studies suggest that thermography is only as accurate as photographic clinical assessments, and is highly dependent on the ambient temperature during measurements [4].…”
Section: Introductionmentioning
confidence: 99%
“…Three‐centimeter brass probes were heated to 100°C and handled with a spring‐loaded insulated device for consistent pressure , which measured 0.9 ± 0.05 kg/cm 2 . Heated probes were applied to the skin within tattoo markings for 25 seconds, which has previously been shown to produce deep partial thickness burns via both histological and noninvasive methods . Twelve wounds were created on each animal, with six on either side of the spine.…”
Section: Methodsmentioning
confidence: 99%
“…102 Photoacoustic imaging was shown to be superior to LDI in detecting burn depth in animals, 103 although a systematic review recently concluded that LDI is superior to other imaging modalities. 104 Other imaging modalities to assess burn depth include near-infrared spectroscopy, 105 ultrasound, 106 skin quality probes, 107 nuclear magnetic resonance imaging 108 capillary microscopy, orthogonal polarization spectral imaging, reflectance mode confocal microscopy, and polarization-sensitive optical coherence. 109 These modalities require further testing before they are used routinely in the clinical setting.…”
Section: Adjuncts To the Clinical Assessment Of Patients With Burnsmentioning
confidence: 99%